APPROACHES AND METHODS OF TEACHING ENGLISH: ORAL APPROACH, SITUATIONAL LANGUAGE TEACHING AND AUDIO-SPEECH METHOD - Khotamova Maftuna Madatovna (Galaxy International Interdisciplinary Research Journal, 2022)
Approaches and methods of teaching English, as well as any foreign language, are currently constantly being reflected and rethought due to the fact that the very understanding of the nature of the language, the ways of learning it, is changing, as well as in response to the growing demand of educational institutions around the world for more effective curricula.